An investigation on the operation of Solid Oxide Fuel Cells and micro-turbine for load-following performances - Palkar Trupti Vikas (2013)
Fuel cells are prominently known and researched extensively by scientists and companies globally for its use as alternative form of energy without any further degradation of Mother Nature. In a few years, the quantity of coal and oil would be reaching an all-time low making it absolutely necessary to find for other viable